2008
DOI: 10.1093/jxb/erm297
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Rubisco forms in proteobacteria: their functional significance in relation to CO2 acquisition by the CBB cycle

Abstract: Rubisco is the predominant enzymatic mechanism in the biosphere by which autotrophic bacteria, algae, and terrestrial plants fix CO(2) into organic biomass via the Calvin-Benson-Basham reductive pentose phosphate pathway. Rubisco is not a perfect catalyst, suffering from low turnover rates, a low affinity for its CO(2) substrate, and a competitive inhibition by O(2) as an alternative substrate. As a consequence of changing environmental conditions over the past 3.5 billion years, with decreasing CO(2) and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
427
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(448 citation statements)
references
References 57 publications
21
427
0
Order By: Relevance
“…Therefore, while both isolates encode Form I and Form II RubisCO genes, it is unlikely that all Zetaproteobacteria do. The presence of Form II rather than Form I is interesting as it is indicative of adaptations to high CO 2 and very low O 2 environments (Badger and Bek, 2008;Tabita et al, 2008), which is consistent with the O 2 profiles presented by Glazer and Rouxel (2009), in which the O 2 levels at Loihi Seamount iron mats were often below the detection limit (3 mM) even at the mat surface. These findings suggest that the broad phylogenetic spectrum of Zetaproteobacteria represented by SAGs analyzed in this study have a lower O 2 tolerance for fixing carbon compared with their cultivated counterparts.…”
Section: Carbon Utilizationsupporting
confidence: 76%
“…Therefore, while both isolates encode Form I and Form II RubisCO genes, it is unlikely that all Zetaproteobacteria do. The presence of Form II rather than Form I is interesting as it is indicative of adaptations to high CO 2 and very low O 2 environments (Badger and Bek, 2008;Tabita et al, 2008), which is consistent with the O 2 profiles presented by Glazer and Rouxel (2009), in which the O 2 levels at Loihi Seamount iron mats were often below the detection limit (3 mM) even at the mat surface. These findings suggest that the broad phylogenetic spectrum of Zetaproteobacteria represented by SAGs analyzed in this study have a lower O 2 tolerance for fixing carbon compared with their cultivated counterparts.…”
Section: Carbon Utilizationsupporting
confidence: 76%
“…This form II RuBisCO is also present in the Saanich Inlet OMZ SUP05 (9) and the clam symbionts Candidatus Ruthia magnifica (18) and Candidatus Vesicomyosocius okutanii (21). In contrast, the H 2 -oxidizing symbionts of Bathymodiolus mussels (4) possess genes for a form I RuBisCO, which is optimized for higher O 2 and lower CO 2 concentration (32). The presence of genes in GB SUP05 encoding for form II RuBisCO enzymes typically adapted to low O 2 and high CO 2 concentrations is consistent with the low O 2 conditions of the deep GB.…”
Section: Resultsmentioning
confidence: 84%
“…Upstream of cbbLS, no genes involved in the CBB cycle were identified (Figure 3). A similar cbb gene cluster with conserved cbbLSQO gene organization has been found in the chemoautotrophic Gammaproteobacteria Thiomirospira crunogena XCL-2, Hydrogenovibrio marinus and the endosymbiont of Solemya velum (Badger and Bek, 2008). It has been observed that the CBB cycle genes of obligate autotrophs apparently do not form CBB operons that would facilitate coordinated regulation, presumably because these genes are constitutively expressed and, therefore, do not require regulation in these obligate autotrophs .…”
Section: Autotrophic Carbon Metabolismmentioning
confidence: 70%